2015
DOI: 10.1007/s00192-015-2847-x
|View full text |Cite
|
Sign up to set email alerts
|

Incontinence medication response relates to the female urinary microbiota

Abstract: Introduction Many adult women have resident urinary bacteria (urinary microbiome/microbiota). In adult women affected by urinary urgency incontinence (UUI), the etiologic and/or therapeutic role of the urinary microbiome/microbiota remains unknown. Hypothesis Microbiome/microbiota characteristics will relate to clinically relevant treatment response to oral UUI medication. Methods Adult women initiating oral medication treatment for UUI and a comparator group of unaffected women were recruited in a tertiar… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

13
188
2
5

Year Published

2016
2016
2021
2021

Publication Types

Select...
9

Relationship

4
5

Authors

Journals

citations
Cited by 219 publications
(220 citation statements)
references
References 27 publications
13
188
2
5
Order By: Relevance
“…This and other emerging knowledge about urinary microbiota may provide information about the absence of good bacteria, as well as the presence (or overabundance) of bad bacteria. In a companion to this study (11), we reported that urine samples from women who did not self-report UTI were likely to be predominated by Lactobacillus, Streptococcus , and Gardnerella , an observation that is consistent with previous reports (8,9,16). In contrast, the urine of women with UTI were more likely to contain traditional uropathogens at the expense of Gardnerella, Streptococcus and Lactobacillus (11), which may be a clue to the composition of healthy microbiota, consistent in part with previous observations (9,16).…”
Section: Discussionsupporting
confidence: 90%
See 1 more Smart Citation
“…This and other emerging knowledge about urinary microbiota may provide information about the absence of good bacteria, as well as the presence (or overabundance) of bad bacteria. In a companion to this study (11), we reported that urine samples from women who did not self-report UTI were likely to be predominated by Lactobacillus, Streptococcus , and Gardnerella , an observation that is consistent with previous reports (8,9,16). In contrast, the urine of women with UTI were more likely to contain traditional uropathogens at the expense of Gardnerella, Streptococcus and Lactobacillus (11), which may be a clue to the composition of healthy microbiota, consistent in part with previous observations (9,16).…”
Section: Discussionsupporting
confidence: 90%
“…In a companion to this study (11), we reported that urine samples from women who did not self-report UTI were likely to be predominated by Lactobacillus, Streptococcus , and Gardnerella , an observation that is consistent with previous reports (8,9,16). In contrast, the urine of women with UTI were more likely to contain traditional uropathogens at the expense of Gardnerella, Streptococcus and Lactobacillus (11), which may be a clue to the composition of healthy microbiota, consistent in part with previous observations (9,16). Given its beneficial role in the genito-urinary tract (1720), Lactobacillus in the bladder may prevent UTI or facilitate microbial restoration following UTI treatment.…”
Section: Discussionsupporting
confidence: 90%
“…However, careful labial toilet was employed, and catheterisation of patients who were at a high risk of bacterial infection was not ethically feasible as per our local ethics committee. Analysis of non-UTI CSU samples in a separate study [17] demonstrated that the urinary diversity of patients with urge incontinence who do not respond to VESIcare is eight times greater than normal controls. Thus, it is reasonable to assume that MSUs collected in our study are not a gross overestimation of urinary diversity.…”
Section: Discussionmentioning
confidence: 99%
“…A few key things are known. First, the FUM are distinct between overactive bladder (OAB) patients and continent controls [21, 31] (Figure 2). Overall, the OAB cohorts tend to be more diverse by culture and sequencing, and have fewer Lactobacillus -dominant profiles.…”
Section: The Female Urinary Microbiota In Relation To Health and Diseasementioning
confidence: 99%